Pengaruh Kualitas Sistem Dan Kualitas Pelayanan Terhadap Manfaat Bersih Aplikasi Mobile Banking Dengan Variabel Intervening Kepuasan Pengguna - Rahayu Saputri; Mellya Embun Baining; Khairiyani Khairiyani (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to test whether system quality and service quality influence user satisfaction and have a net beneficial impact on mobile banking application users. The type of research in this research is quantitative. The results of this research show that there is a significant influence on system quality on user satisfaction, there is a significant influence on service quality on user satisfaction, there is a significant influence on system quality on net benefits, there is no significant influence on service quality on net benefits, there is no significant influence on user satisfaction on net benefits, user satisfaction is unable to mediate system quality on net benefits is not significant, and user satisfaction is not able to mediate service quality on net benefits is not significant.